ANALISIS KEPUTUSAN ADOPSI TEKNOLOGI QRIS PADA PEDAGANG KAKI LIMA: PERSPEKTIF PENGGUNA DAN NON- PENGGUNA - Dewi Prahastiwi Indi Armani; Theodorus Sendjaja (Fakultas Teknik dan Informatika Universitas PGRI Mahadewa Indonesia, 2025)
Technology is influencing the way of life and interactions of people around the world, including Indonesia. This includes technological developments in the financial sectors, commonly known as financial technology (fintech). The National Non-Cash Movement has been also launched by Bank Indonesia since 2014, with one of the commonly used digital platforms currently being the Quick Response Code Indonesia Standard (QRIS). QRIS is easily accessible to various groups, including MSMEs and informal traders, which can encourage financial inclusion. However, in reality, QRIS usage in some regions, especially for MSMEs and informal traders/ street vendors is very low. This study fills the gap by focussing on the smallest informal sectors, namely street vendors as QRIS users and non-users. With a thematic analysis focussing on technical and managerial aspects. This resulted in an analysis of what factors influence a decision in using QRIS from the perspective of users and non-users. The researcher conducted direct interviews with five QRIS users and five non-users. The research results is the influencing factors QRIS users is the convenience of transaction and consumer motivation. Meanwhile, what influence non-QRIS users is the lack of technical knowledge and concerns regarding security.